ACE inhibitory activities of two peptides derived from Volutharpa ampullacea perryi hydrolysate and their protective effects on H2O2 induced HUVECs injury. (July 2022) - Wang, Chen-Xin; Song, Cheng-Cheng; Liu, Xin-Tong; Qiao, Bian-Wen; Song, Shuang; Fu, Ying-Huan
Graphical abstract: These two enzymatic hydrolysis peptides are potential ACE inhibitors, which inhibit the C-domain more than the N-domain. Besides, two peptides are able to protect HUVECs against peroxide-induced oxidative stress by activating the HO-1/Nrf2 pathway, thereby reducing the accumulation of ROS. Highlights: Two enzymatic hydrolysis peptides, IVTNWDDMEK and VGPAGPRG, derived from Volutharpa ampullacea perryi, are novel ACE inhibitory peptides with antioxidant properties. The two enzymatic hydrolysis peptides inhibited the C structural domain significantly more than the N structural domain. Both enzymatic hydrolysis peptides were able to protect HUVECs from H2 O2 -induced cell damage by employing the Nrf2/HO-1 pathway. Our study shows that two enzymatic hydrolysis peptides are food-derived ingredients that can be used to control hypertension. Abstract: The purpose of this study is to explore the effects of IVTNWDDMEK and VGPAGPRG, two angiotensin I-converting enzyme (ACE) inhibitory peptides purified from Volutharpa ampullacea perryi, on ACE's two domains and on nitric oxide (NO), endothelin-1(ET-1) production in human vascular endothelial cells (HUVECs). In addition, we sought to investigate the effects of these two peptides on HUVECs injury induced by H2 O2 . The results indicated that the inhibition of the ACE C-domain was significantly higher than that of the ACE N-domain by these two peptides. Molecular dynamics (MD) analysis revealed that the hydrogen bonds interactions between ACE and two peptides, the chelation between peptides and Zn 2+ both play important role, which might contribute significantly to the ACE inhibitory activity. Two peptides significantly increase NO and ET-1 production in a dose-dependent manner and protects against hydrogen peroxide-induced HUVEC cell injury. The reported results also show that two peptides up-regulated the expression of nuclear factor erythroid 2-related factor (Nrf2) and heme oxygenase-1 (HO-1), and reduce the accumulation of reactive oxygen species (ROS) and malondialdehyde (MDA). Our study indicated that IVTNWDDMEK and VGPAGPRG could be potent ACE inhibitors and Volutharpa ampullacea perryi is a good source of bioactive peptides, which provided a theoretical basis for the broad application of two selected peptides as functional food with anti-hypertensive activity.